Estetika Dan Filsafat Instrumen Kempyung Sebagai Kunci Dalam Gamelan Semara Pagulingan - Fenty, Ni Ketut; Wisarja, I Ketut; Marsono (Metta : Jurnal Ilmu Multidisiplin, 2023)
Gamelan semara pagulingan uses a seven-tone pelog tuning consisting of five principal tones (O E U A I) and two pemero tones (ndeung and ndaing). This study aims to discover the meaning and philosophy of the kempyung instrument, which is considered the key in the gamelan semara pagulingan Banjar Pagan Kelod. The method used is qualitative research carried out in several stages: preparation, data collection, and data analysis. The study results found a concept of two-tone distance in this part of the crew called basang metundun. Basang metundung, which, compared to humans, is the stomach and back. The stomach and back are found in parts of the human body and are located on the front (basang) and back (tundun); this also follows the context of life in society. The kempyung instrument has a meaning which is symbolized as a key or something that makes a piece harmonious. In Lontar Aji Prakempa, it is stated that the balance of human life is in the dualistic dimension, namely believing in the existence of two powerful forces such as good and evil, day and night, male and female, kaja and kelod, sekala and niskala, and so on. In the teachings of Hinduism, it is known as rwa bhineda, which means two different and opposite things, but when balanced, they become something harmonious.